The Role of Financial Knowledge and Personality on Financial Management Behavior - Yusup, Raihany; Jasuni, Ana Yuliana (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Understanding the intricate interplay between financial knowledge, personality traits, and financial management behavior is crucial for the success of small businesses, especially in the vibrant world of Pecel Lele SMEs in Sukabumi Regency. This study delves into this dynamic relationship, drawing data directly from 50 SMEs in Sukabumi. Contrary to expectations, individual analysis reveals that financial knowledge alone does not significantly impact financial management behavior. However, a fascinating discovery emerges when considering personality traits; they wield a substantial influence on the financial decisions made by Pecel Lele SME owners. Yet, the true revelation lies in the combined effect of personality traits and financial knowledge. Together, they emerge as potent drivers, shaping decision-making processes and financial management behaviors within these enterprises. This research offers valuable insights into the intricate fabric of factors shaping the financial landscape of Pecel Lele SMEs, paving the way for more informed strategies and interventions to bolster their success in Sukabumi and beyond. The data analysis was conducted using multiple linear regression through SPSS version 26 software.